Speaker Jim Wright Power, Scandal, and the Birth of Modern Politics - Flippen, J. Brooks (University of Texas Press, 2021)
Jim Wright made his mark on virtually every major public policy issue in the later twentieth century-energy, education, taxes, transportation, environmental protection, civil rights, criminal justice, and foreign relations, among them. He played a significant role in peace initiatives in Central America and in the Camp David Accords, and he was the first American politician to speak live on Soviet television. A Democrat representing Texas's twelfth district (Fort Worth), Wright served in the US House of Representatives from the Eisenhower administration to the presidency of George H. W. Bush, including twelve years (1977-1989) as majority leader and speaker. His long congressional ascension and sudden fall in a highly partisan ethics scandal spearheaded by Newt Gingrich mirrored the evolution of Congress as an institution. Speaker Jim Wright traces the congressman's long life and career in a highly readable narrative grounded in extensive interviews with Wright and access to his personal diaries. A skilled connector who bridged the conservative and liberal wings of the Democratic party while forging alliances with Republicans to pass legislation, Wright ultimately fell victim to a new era of political infighting, as well as to his own hubris and mistakes. J. Brooks Flippen shows how Wright's career shaped the political culture of Congress, from its internal rules and power structure to its growing partisanship, even as those new dynamics eventually contributed to his political demise. To understand Jim Wright in all his complexity is to understand the story of modern American politics